Arab Pension Systems : Trends, Challenges and Options for Reforms - Arab Monetary Fund; World Bank Group (World Bank, Washington, DC, 2017)
This report provides an overview of current pension challenges and opportunities formembers of the Arab Monetary Fund (AMF)1. There is an urgent need to address pensionissues in the region to address fiscal, macroeconomic, sustainability, equity and welfarechallenges. The report sets out potential solutions and proposals that countries could adopt toimprove their pension outcomes. The analysis and the reforms grew out of the high-levelconference: “Arab Pension Reforms,” that took place on January 25th, and 26th, 2017, in AbuDhabi. The conference was co-hosted by the AMF and the World Bank Group (WBG).